Ekspresi Bcl-2 pada Karsinoma Urotelial Kandung Kemih dan Hubungannya dengan Berbagai Faktor Prognosis - Hendy Setyo Yudhanto; Budiana Tanurahardja; Puspita Eka Wuyung (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2019)
BackgroundUrothelial carcinoma comprises of 90% of all cases in bladder. There are two groups which are non invasivedepend on whether the tumor has reached muscularis mucosa. 5-Years survival rate depend on grading andstaging. Low malignant grade and non invasive may reach 90% survival rate, with recurrence rate 40-60%. Highmalignant grade and invasive tumor has only10-17% survival rate. Mitosis and lymphovascular invasion arerelated with recurrency. However, there are some controvesi regarding Bcl-2 expression in bladder urothelialcarcinoma. This study was aimed to evaluate different expression of Bcl-2 with 4 related factors contributed tosurvival, which are degree of malignancy, stage, mitosis, and lymphovascular invasion.MethodsA retrospective cross sectional study on urothelial carcinoma of the bladder was conducted in the Departmentof Anatomical Pathology, Faculty of Medicine, University of Indonesia/RSCM. The cases were collected fromthe year of 2010 to 2014. In this study 21 cases of low grade and 21 cases of high high grade were found. Bcl-2immunohistochemistry staining performed in all cases and percentages are calculated to make 0-3 scoring.ResultsMost case is fifth decade as many as 27 cases. Obtained 4 cases found limfovaskuler invasion. This studyobtains the relationship between mitosis with grade of tumor (p: 0.000). the result suggests that there are nodifferences between the expression of Bcl-2 with the degree of malignancy stage, mitosis and lymphovascularinvasion.